ANALISA PROSEDUR MONITORING KINERJA KARYAWAN PADA BAGIAN PRODUKSI PT TOKAI RUBER AUTO HOSE INDONESIA - Tri Winarto; Amri Rahmawati (JURNAL LENTERA BISNIS, 2025)
This study was conducted to determine the monitoring of employee performance in the production department at PT Tokai Rubber Auto Hose Indonesia. The purpose of this study was to determine the monitoring procedure, obstacles and solutions in monitoring employee performance in the production department at PT Tokai Rubber Auto Hose Indonesia. The data collection technique was through observation, namely directly observing the object being studied. The obstacles to the monitoring procedure for employee performance in the production department at PT Tokai Rubber Auto Hose Indonesia were that in the production process, employees did not follow the SOP and were often late to enter the line. The temporary solution was to evaluate and supervise employee activities in understanding good procedures.